Position and Possessions: Stratification Economics and Intergroup Inequality - Darity, William A. (Journal of Economic Literature, 2022)
This article provides an overview of the origins and development of stratification economics as a subfield that centers the importance of identity, social ranking, and relative group position. Stratification economics developed in response to explanations for interracial/ethnic/gender inequality that invoked group-based dysfunction on the part of the subordinate community. Influences, detailed here, include the works of W. E. B. DuBois, Thorstein Veblen, Karl Marx, Eric Williams, Herbert Blumer, Claude Steele, Cecilia Ridgeway, Thomas Pettigrew, and Linda Tropp. The article concludes with an exploration of unique insights and extensions stratification economics affords a variety of themes: the impact of multiple identities, the determinants of individual productivity, variation in intensity of group identification, “passing,” sources of intergroup differences in wealth, and social mobility and immigration. (JEL D31, D63, I31, J15, J16, Z13)